Theoretical basis for an economic evaluation of road accident losses - Kapskij, Denis; Samoilovich, Tatyana (Transport, 2009)
The article regards the theoretical basis for estimating life value for the purpose of calculating road accident losses. The paper presents a simple structure of accident costs that could be taken into account in order to calculate the total economic value of road accidents. The article also shows the basic methods of estimating life value in different countries for different purposes and describes the problems of estimating life value in the Republic of Belarus. The paper comprises practically used values of life and the costs of injuries in some countries. Losses and costs caused by a road accident are regarded as direct and indirect. Besides, losses occurring during a road accident are considered as economic and social. The temporary estimated values of the total economic value of road accidents are discussed at the end of the article. First published online: 27 Oct 2010